From Harry to Garri: Strategies for the Transfer of Culture and Ideology in Russian Translations of Two English Fantasy Stories - Inggs, Judith (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2003)
Abstract This article focuses specifically on two examples of fantasy stories and their translations into Russian: The Lion, the Witch, and the Wardrobe (Lewis 1950), a classic English fantasy story, and Harry Potter and the Philosopher’s Stone (Rowling 1997), a modern blending of fantasy with the traditional English school story. The analysis shows that the approach to translation is largely random. In the translations of The Lion, the Witch and the Wardrobe, there is some evidence of simplification as a strategy, and some confusion over the appropriate translation of cultural items in the translations of Harry Potter and the Philosopher’s Stone. Generally, however, the translators are shown not to have attempted to situate the stories in a Russian context, and have retained intact both the cultural backdrop and the moral values put forward in the works. A study of the reception of such works by young readers would provide valuable information about the success or failure of the translations discussed in this article.